2010
DOI: 10.1007/s11249-010-9716-z
|View full text |Cite
|
Sign up to set email alerts
|

Elastic–Plastic Spherical Contact Modeling Including Roughness Effects

Abstract: The effect of material properties and surface roughness on the contribution of asperities and sphere bulk displacements to the total displacement of a rough spherical contact is investigated. A dimensionless transition load, above which the contribution of the bulk displacement exceeds the contribution of the asperities displacement, is found as a function of the plasticity index and dimensionless critical interference of the sphere bulk. A criterion is proposed for evaluating the importance of surface roughne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…2 yields values of the shell parameter k about 1 for both dimple types. Therefore, the following analysis for the rough dimple contact behavior will be based on a rough solid sphere contact model presented in reference [31]. The critical load P c at yield inception can be obtained from Eq.…”
Section: Comparison Between Experimental and Theoretical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 yields values of the shell parameter k about 1 for both dimple types. Therefore, the following analysis for the rough dimple contact behavior will be based on a rough solid sphere contact model presented in reference [31]. The critical load P c at yield inception can be obtained from Eq.…”
Section: Comparison Between Experimental and Theoretical Resultsmentioning
confidence: 99%
“…Hence, the bulk of the dimples under examination is elastically deformed and can be analyzed as a solid sphere in elastic contact. Figure 11 presents an equivalent rough spherical contact model that was studied theoretically by Li et al [31]. In reference [31], a model was developed for the effect of the dimensionless normal load P * , the dimensionless critical interference x à c and the plasticity index w, on the individual contributions of the sphere bulk and the asperities to the total displacement of a rough spherical contact.…”
Section: Comparison Between Experimental and Theoretical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the roughness of the bridge is much inferior to that of the bump, only the roughness of the bump is taken into account; Which gives a contact between a spherical rough surface and a flat surface. Unlike contact between nominally flat surfaces, in a spherical rough contact, both contact asperities and the bulk deform under normal load [13]. Several works on spherical contact are found in the literature, while most of them deal with the contact between a rough flat and a smooth spherical [14][15], further the displacement is assumed to be elastic and/or purely plastic.…”
Section: A Contact Of Rough Surfacesmentioning
confidence: 99%
“…The work [16] studied the spherical rough contacts, with the deformation of asperities assumed to be purely plastic. More recently, references are given as, [13] and [17] analyzed the contact of a rough sphere and a rigid flat, with elastic, elastic-plastic and fully plastic regime considered for the deformation of the sphere and the asperities; however, the roughness of the sphere was transferred to the flat. Reference [18] found that the flatten models predict larger contact areas and higher loads than the indentation model at the same interference, and they cannot be replaced by each other.…”
Section: A Contact Of Rough Surfacesmentioning
confidence: 99%